Evaluasi Implementasi Manajemen Berbasis Sekolah Di UPT SPF SMP Negeri 22 Kota Makassar: Sebuah Analisis Kualitatif - Indriati Amirullah; Noerhayati Amirullah; Anne Abdurrahman; Nurasia Natsir (UNIVERSITAS MARITIM AMNI SEMARANG, 2023)
This research aims to explore strategies and challenges in implementing School Based Management (MBS) at UPT SPF SMP Negeri 22 Makassar City. Through a qualitative research approach, data was collected through in-depth interviews, participant observation, and document analysis. The research results show that schools have adopted a number of strategies to implement SBM, including increasing stakeholder participation, using technology in the teaching and learning process, and increasing transparency and accountability. However, the research also uncovered a number of challenges, including resistance to change, lack of training and support for school staff, and resource constraints. This research suggests that effective solutions to these challenges are essential to ensure successful and sustainable SBM implementation.